O programa de educação estética e artística - PEEA : 2010-2017 : o lugar da Expressão Plástica no Currículo do 1º Ciclo do Ensino Básico - Ferreira, Tânia Sofia Afonso (2019)
The present dissertation has as main purpose to know and clarify the context and circumstances in which the Program of Aesthetic and Artistic Education (PEEA) appeared in the Portuguese educational panorama (2010-17). On the one hand, we sought to describe the events that preceded the creation of the PEEA (2010) and, on the other hand, to identify its main authors and / or actors, their conceptual influences, their assumptions and programmatic objectives, with a view to contribute to a better knowledge of this educational project and to understand its models of implementation and action (and possible impacts) in the school context, more concretely, in the disciplinary area of the so-called Visual Expressions in the Primary Education. First, there were mapped the main authors, theoretical issues and historical moments of art education (national and international) that influenced the conceptual and empirical assumptions on which the creation of the PEEA were justified. In the 1990s, in Portugal, discourses and documents (educational and political) emerged that point to the need for serious intervention in this area, from the National Education Council’s Opinions (1992 and 1999) to the recommendations of Teachers’ Associations, Organizations International and other ‘specialists’ in Arts Education. Secondly, the focus of the research focused on the intervention areas of the PEEA and the specificities of Teacher Training in the Visual Arts area. In this context, the educational models proposed in the Integrated Program of Visual Arts: The First Look from the influences of the American Model Discipline-Based Art Education (DBAE), which support the theoretical basis of the PEEA, are discussed. Finally, there is the Artistic